Analysis Of Pregnant Women's Noncompliance With Iron Supplementation - Siska Sandra Masulili; Nila Widya Keswara (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Anemia during pregnancy is a significant public health issue that affects both maternal and fetal health, despite the implementation of the Iron Supplement Tablet (IST) program. One major challenge is the non-compliance of pregnant women in taking IST. This study aimed to analyze factors associated with non-compliance in IST consumption among pregnant women in the working area of the Popayato Timur Community Health Center. A quantitative observational analytical design with a cross-sectional approach was used, involving a sample of 40 pregnant women in their third trimester, selected using a total sampling technique. Data were collected using structured questionnaires and a review of maternal and child health records, covering respondent characteristics, knowledge levels, and IST consumption compliance. Results indicated that 55% of pregnant women were non-compliant in consuming IST. Multivariate analysis revealed that maternal knowledge was significantly associated with IST consumption compliance (p = 0.012; OR = 7.05). Pregnant women with good knowledge were more likely to comply compared to those with low knowledge. Age, parity, and occupation showed no statistically significant relationship. In conclusion, maternal knowledge was the most dominant factor influencing compliance with iron tablet consumption. Strengthening education and counseling during antenatal care is crucial for improving IST compliance and preventing anemia in pregnant women.